Comparative Transcriptomic and Metabolic Analyses Reveal the Molecular Mechanism of Ovule Development in the Orchid, Cymbidium sinense - Zeng, Danqi; Que, Caixia; Teixeira da Silva, Jaime A.; Xu, Shutao; Li, Dongmei (Frontiers in Plant Science, 2022)
Ovule development is pivotal to plant reproduction and seed development. Cymbidium sinense (Orchidaceae) has high ornamental value due to its pleasant aroma and elegant floral morphology. The regulatory mechanism underlying ovule development in orchids, especially C. sinense, is largely unknown and information on the C. sinense genome is very scarce. In this study, a combined analysis was performed on the transcriptome and non-targeted metabolomes of 18 C. sinense ‘Qi Jian Hei Mo’ ovule samples. Transcriptome analysis assembled gene-related information related to six growth stages of C. sinense ovules (S1-S6, equivalent to 30, 35, 42, 46, 53, and 60 days after pollination). Illumina sequencing technology was used to obtain the complete set of transcriptome sequences of the 18 samples. A total of 81,585 unigene sequences were obtained after assembly, 24,860 (30.47%) of which were functionally annotated. Using transcriptome sequencing technology, a total of 9845 differentially expressed unigenes (DEUs) were identified in C. sinense ovules that were assigned to specific metabolic pathways according to the Kyoto Encyclopedia of Genes and Genomes (KEGG). DEUs associated with transcription factors (TFs) and phytohormones were identified and analyzed. The TFs homeobox and MADS-box were associated with C. sinense ovule development. In particular, the phytohormones associated with DEUs such as indole-3-acetic acid (IAA), cytokinin (CK), gibberellin (GA), abscisic acid (ABA), brassinosteroid (BR), and jasmonate (JA), may have important regulatory effects on C. sinense ovule development. Metabolomic analysis showed an inconsistent number of KEGG annotations of differential metabolites across comparisons (S2_vs_S4, S2_vs_S5, and S4_vs_S5 contained 23, 26, and 3 annotations, respectively) in C. sinense ovules. This study provides a valuable foundation for further understanding the regulation of orchid ovule development and formation, and establishes a theoretical background for future practical applications during orchid cultivation.